Traditional Chinese Medicine Bionic Tiger Bone Powder for the Treatment of AI-Associated Musculoskeletal Symptoms. (31st January 2017) - Li, Yifan; Zhang, Zhenhua; Cui, Feifei; Liu, Jialing; Wang, Yitong; Jiang, Juling; Ma, Wenxin; Lu, Wenping
Abstract : Background . Aromatase inhibitors (AIs) are used for adjuvant therapy of breast cancer; however AIMSS (AI-Associated Musculoskeletal Symptoms) can negatively affect quality of life and compliance. Most patients in China moved to TCM (traditional Chinese medicine) for help. TB (tiger bone) is used to treat bone disease, whose main ingredients are calcium and collagen. The objective of this study was to evaluate whether the TB prevented AIMSS in postmenopausal women with ER/PR+ breast cancer. Methods . We conducted a randomized, blind, controlled study of comparing TB versus placebo for 12 weeks in postmenopausal women with breast cancer who have taken AI for less than a month. Patients completed the M-BPI, VAS, and FACT-B at baseline, 6 weeks, and 12 weeks. M-BPI and VAS were used as the primary outcomes. FACT-B was used as the secondary outcome. Serum E 2 and FSH were tested every 6 weeks. Results . Of 70 evaluable cases, 8 of 35 patients (22.9%) developed new or worsening point symptoms in TB group, compared to 21 of 35 (60%) in placebo group (P < 0.001 ). We also found differences between 2 groups in average pain (2 to 5.6), worst pain (3.9 to 8), pain interference severity (1.9 to 5.3), stiffness (2.4 to 6.9), and joint symptom interference (1.8 to 5.7), all P < 0.001 ; similar findings were seen in VAS value (3 to 6.6) at the end of intervention. HRQoL measured by FACT-B (P < 0.05 ) was improved. No change of serum estradiol and FSH between two groups. Conclusions . TB appeared to be effective and safe in the prevention of AIMSS. This trial is registered with ChiCTR-IPR-15007081 .